HIKING INCIDENTS DATABASE STRUCTURE USING ENTITY-RELATIONSHIP DIAGRAM (ERD) - Norsyazlin Mohd Rosli; Nur Shaffiqa Muhammad Soffian; Amelia Ahmad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The use of Geographic Information System (GIS) database system during Search and Rescue (SAR) operations aims to improve search efficiency and effectiveness while also minimizing operating expenses and response times to identify the mission subject as rapidly as possible. However, in Malaysia, the use of GIS for SAR operation is very restricted. Nowadays, in Malaysia, SAR operation for hiking incidents have occurred frequently whether the incidents happen because of environment factors, human factors, or weather factors. In order to prevent, avoid and reduce the hiking incidents cases, we need to develop a database structure which can be specifically used by hikers, guiders, and SAR team in preparing for SAR operations of any situation. This paper discusses the potential of Entity-Relationship Diagram (ERD) in developing a database structure for hiking incidents. We apply content analysis of literature that will focus on illustrating the three (3) main stages, namely identifying the type of data required, forming entities and attributes, and identifying the relationship between the entities on hiking incidents database. By constructing this database, it is possible to avoid and reduce incidents during hiking and contribute to better preparation for hikers, guider, and SAR team operation.